Bam32/DAPP1-Dependent Neutrophil Reactive Oxygen Species in WKYMVm-Induced Microvascular Hyperpermeability - Hao, Li; Marshall, Aaron J.; Liu, Lixin (Frontiers in Immunology, 2020)
B cell adaptor molecule of 32 kDa (Bam32), also known as dual adapter for phosphotyrosine and 3-phosphoinositides 1 (DAPP1), has been indicated in regulating lymphocyte proliferation and recruitment during inflammation. Its role in neutrophils during inflammation remains unknown. Using intravital microscopy, we examined the role of Bam32 in formyl peptide WKYMVm-induced permeability changes in post-capillary venules and assessed simultaneously neutrophil adhesion and emigration in cremaster muscles of Bam32-deficient (Bam32-/-) and the wild-type (WT) control mice. We observed significantly reduced WKYMVm-induced microvascular hyperpermeability accompanied by markedly decreased neutrophil emigration in Bam32-/- mice. The Bam32-specific decrease in WKYMVm-induced hyperpermeability was neutrophil-dependent as this was verified in bone marrow transplanted Bam32 chimeric mice. We discovered that Bam32 was critically required for WKYMVm-induced intracellular and extracellular production of reactive oxygen species (ROS) in neutrophils. Pharmacological scavenging of ROS eliminated the differences in WKYMVm-induced hyperpermeability between Bam32-/- and WT mice. Deficiency of Bam32 reduced WKYMVm-induced ERK1/2 but not p38 or JNK phosphorylation in neutrophils. Inhibition of ERK1/2 signaling cascade suppressed WKYMVm-induced ROS generation in WT neutrophils and microvascular hyperpermeability in WT mice. In conclusion, our study reveals that Bam32-dependent, ERK1/2-involving ROS generation in neutrophils is critical in formyl peptide-induced microvascular hyperpermeability during neutrophil recruitment.